Menilik Nilai Illahiyat Dalam Konsep Kecermatan Maksimun Pada Sistem Respirasi Manusia - Winarto, Yoga Agustian Permadi (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2023)
Integration is the process of combining several separate parts into a unified whole or whole. Integration is not just a formality in combining scientific and Islamic knowledge, but also includes efforts to bring together perspectives, ways of thinking and ways of acting between the two. In the view of Islam, science and nature have a balance with religion which implies the intention to pursue scientific knowledge by Muslims. As the universe itself is seen in the Qur'an as a collection of signs of His power. One of the signs of God's power that is interesting to study in an integrative manner from a scientific and Islamic point of view is the human respiratory system, where this system is one of the most important systems in the survival of living things, especially humans. The purpose of this study is intended to bridge scientific studies and practice. This research was conducted through the method of literature review from various sources, including the Al-Quran as the most important scientific source in Islam with the study of scientific thematic interpretations. The results of this study show the important role of respiration in living things and its relation to the power of Allah SWT regarding the concept of creation which follows the principle of maximum accuracy, where the explanation of this is also supported by His words in the Al-Quran.